2023
DOI: 10.3389/fmicb.2023.1120838
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of gut DNA viromes in wild and captive Himalayan vultures

Abstract: IntroductionHimalayan vultures (Gyps hinalayensis) are widely distributed on the Qinghai-Tibetan Plateau and play a crucial role in maintaining the ecological balance by feeding on decayed corpses of wild and domestic animals. Large-scale culture and metagenomics studies have broadened our understanding of viral diversity in animals’ gastrointestinal tracts. However, despite the importance of gut viral communities in regulating bacterial diversity and performing symbiotic functions, no gut viral study has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Furthermore, the living environment is also a crucial factor influencing the host gut phage community [59,122]. Limited previous research evidence in species such as vulture (Gyps hinalayensis) [123], Tasmanian devil (Sarcophilus harrisii) [124], and giant panda (Ailuropoda melanoleuca) [59] have indicated that controlled captive environments (e.g., dietary changes, microbial transmission, and human interference) can alter the composition and diversity of the host gut phage community. We speculate that the unique captive environment of giant pandas [4,16,52,61,104,125,126], characterized by factors such as a high-starch and -milkfat diet, increased antibiotic usage, and frequent human contact, may contribute in part to the pivotal role of phages in shaping the coexistence pattern of the gut bacterial and phage communities in captive giant pandas.…”
Section: Interactions Between Gut Bacterial and Phage Communitiesmentioning
confidence: 99%
“…Furthermore, the living environment is also a crucial factor influencing the host gut phage community [59,122]. Limited previous research evidence in species such as vulture (Gyps hinalayensis) [123], Tasmanian devil (Sarcophilus harrisii) [124], and giant panda (Ailuropoda melanoleuca) [59] have indicated that controlled captive environments (e.g., dietary changes, microbial transmission, and human interference) can alter the composition and diversity of the host gut phage community. We speculate that the unique captive environment of giant pandas [4,16,52,61,104,125,126], characterized by factors such as a high-starch and -milkfat diet, increased antibiotic usage, and frequent human contact, may contribute in part to the pivotal role of phages in shaping the coexistence pattern of the gut bacterial and phage communities in captive giant pandas.…”
Section: Interactions Between Gut Bacterial and Phage Communitiesmentioning
confidence: 99%